Enhanced Passive Safety Surveillance (EPSS) confirms an optimal safety profile of the use of MF59(®)‐adjuvanted influenza vaccine in older adults: Results from three consecutive seasons - Panatto, Donatella (Influenza Other Respir Viruses, 2019)
BACKGROUND: In Europe, the enhanced safety surveillance (ESS) of seasonal influenza vaccines is mandatory, in order to detect any potential increase in reactogenicity when the vaccine composition is updated. The MF59(®)‐adjuvanted influenza vaccine (Fluad™) is the first and the only licensed adjuvanted seasonal influenza vaccine in Europe. OBJECTIVE: Our objective was to summarize the safety data of Fluad™ over three consecutive seasons. METHODS: A passive approach to ESS (EPSS) was adopted, in which reporting of spontaneous adverse events (AEs) by vaccinees and vaccine exposure was estimated, in order to generate a near real‐time reporting rate. EPSS was conducted in Italy during the 2015, 2016, and 2017 influenza seasons in the primary care setting. All AEs reported within 7 days following immunization were analyzed by season, type and seriousness. Fisher's exact test was used to compare frequencies between seasons. RESULTS: Total exposure accounted for approximately 1,000 doses of Fluad™ for each season. A total of 0.5% (2015), 0.7% (2016), and 0.5% (2017) individual case safety reports (ICSRs) were received, corresponding to a total of 9 (2015), 18 (2016), and 12 (2017) spontaneous AEs. The frequencies of AEs of interest were below those expected on the basis of the known safety profile of the vaccine. Most AEs were mild‐to‐moderate in severity. No between‐season difference was found. CONCLUSIONS: Our analyses confirmed that the safety data observed were consistent with the known safety profile of Fluad™, which has been amply established over the last 20 years. No significant changes in the safety profile were observed.